Resolvin E1's Antimicrobial Potential Against Aggregatibacter Actinomycetemcomitans - Abdullatif, Fahad A.; Almaarik, Basmah; Al-Askar, Mansour (Frontiers in Oral Health, 2022)
Background Microorganisms along with host response play a key role in the development of periodontal and peri-implant infections. Advanced periodontal and peri-implant diseases are most likely associated with bacterial plaques that trigger host immune response and eventually lead to the destruction of the attachment apparatus and bone loss around a tooth or a dental implant. A recent systematic review and meta-analysis revealed that Aggregatibacter actinomycetemcomitans had the highest association with peri-implantitis. Resolvin E1 (RvE1) is part of the specialized pro-resolving lipid mediator family biosynthesized from omega-3, polyunsaturated fatty acids (PUFAs), and eicosapentaenoic acid (EPA). Although RvE1 is an established anti-inflammatory agent, it was found that its application as a treatment or as a preventive drug had an indirect effect on the subgingival microbiota of both rats and rabbits with experimental periodontitis. Aim The aim of this study is to evaluate the direct antimicrobial effect of RvE1 on Aggregatibacter actinomycetemcomitans bacteria. Materials and Methods The study comprised three groups that underwent minimum inhibitory concentration (MIC) against Aggregatibacter actinomycetemcomitans. The first group was tested with the RvE1 working concentration of 5 ug/ml, the second group was tested with ethanol (EtOH), 10% as the working concentration, and the final group was diluted in phosphate-buffered saline (PBS) as the positive control. Optical density (OD600) was used for the comparison of bacterial growth among the tested groups. The experiment was conducted in three biological replicates. Data were analyzed using SPSS, and results were analyzed by using one-way analysis of variance (ANOVA) followed by post-hoc Bonferroni using a minimum level of significance (P-value) of 0.05. Results Minimum inhibitory concentration was 1.25 μg/ml and 5% for RvE1 and EtOH, respectively. RvE1's mean optical density (OD600) was 0.156 ± 0.021 and was significantly lower compared with all the other groups (P-value < 0.01). The EtOH group (mean OD600 0.178 ± 0.013) and the PBS group (mean OD600 0.1855 ± 0.022) did not reveal a significant difference (P-value = 0.185). Conclusion RvE1 demonstrated significant antimicrobial activity against A. actinomycetemcomitans with an MIC of 1.25 μg/ml. The RvE1 group showed significantly lower bacterial growth compared to the EtOH and PBS groups.